Visceral Mycotic Aneurysm: Superior Mesenteric Artery Aneurysm Caused by K. pneumoniae - Reham Almasoud; Alaaeddin Nwilati; Saeb Bayazid; Mamoun Shafaamri (Dubai Medical Journal)
We herein report a rare case of mycotic aneurysm of the superior mesenteric artery caused by Klebsiella pneumoniae. A 66-year-old man, a known case of hypertension and aorto-oesophageal fistula with stented aorta in 2010 and 2018, presented to the emergency department multiple times over 2 months with severe postprandial abdominal pain associated with vomiting and fever. On his last presentation, the obtained blood cultures grew ESBL positive K. pneumoniae and a repeated computed tomography (CT) showed a growing aneurysm at the origin of the ileocecal branch of the superior mesenteric artery measuring 17 × 10 mm (the aneurysm was 8 × 7.5 mm in the CT angiography on the previous admission). Extensive workup did not reveal the underlying cause of the mycotic aneurysm, thus we believe the cause to be the infected aortic stent, leading to bacteraemia and vegetations to the mesenteric artery causing the aneurysm. The management plan was placed by a multidisciplinary team consisting of vascular surgeons and infectious disease specialists along with review from a dietician to evaluate the patient’s nutritional status. The patient was started on total parenteral nutrition due to his postprandial pain and on antibiotic therapy according to the infectious disease team’s recommendation. He underwent surgical resection of the mycotic aneurysm, which showed a thrombosed aneurysm in the jejunoileal mesenteric area. The histopathology of the resected tissue demonstrated inflammatory aneurysm of the mesenteric artery. Following the surgery, the patient continued his antibiotic therapy and was discharged on the 13th post-operative day with follow-up appointments in the vascular surgery and infectious disease clinic.